Acute effects of riociguat in borderline or manifest pulmonary hypertension associated with chronic obstructive pulmonary disease - Ghofrani, Hossein Ardeschir; Grünig, Ekkehard (Pulmonary circulation, 2015)
Riociguat is the first oral soluble guanylate cyclase stimulator shown to improve pulmonary hemodynamics in patients with pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension (PH). This pilot study assessed the impact of a single dose of riociguat on hemodynamics, gas exchange, and lung function in patients with PH associated with chronic obstructive pulmonary disease (COPD). Adults with COPD-associated borderline or manifest PH (pulmonary vascular resistance > 270 dyn·s·cm−5, mean pulmonary artery pressure ≥ 23 mmHg, ratio of forced expiratory volume in 1 second [FEV1] to forced vital capacity < 70%, and partial pressure of oxygen and carbon dioxide in arterial blood > 50 and ≤ 55 mmHg, respectively) received riociguat 1 or 2.5 mg during right heart catheterization. Twenty-two patients completed the study (11 men, 11 women, aged 56-82 years; 1-mg group: n = 10 [mean FEV1: 43.1%]; 2.5-mg group: n = 12 [mean FEV1: 41.2%]). Riociguat caused significant improvements (P < 0.01) from baseline in mean pulmonary artery pressure (1 mg: −3.60 mmHg [−11.44%]; 2.5 mg: −4.83 mmHg [−14.76%]) and pulmonary vascular resistance (1 mg: −58.32 dyn·s·cm−5 [−15.35%]; 2.5 mg: −123.8 dyn·s·cm−5 [−32.96%]). No relevant changes in lung function or gas exchange were observed. Single doses of riociguat were well tolerated and showed promising hemodynamic effects without untoward effects on gas exchange or lung function in patients with COPD-associated PH. Placebo-controlled studies of chronic treatment with riociguat are warranted.